Highly-sensitive capture of circulating tumor cells using micro-ellipse filters - Hongmei Chen (Nature Portfolio, 2017)
Abstract Circulating tumor cells (CTCs) detection, enumeration and characterization with microfluidic chips has critical significance in cancer prognosis offering a non-invasive “liquid biopsy”. Based on physical differences of size and deformability, we explore micro-ellipse filters consisting of microfuidic slits in series gradually narrowed. Slender tunnels sensitively capture tumor cells with slim chance to escape. Tumor cells could reside at capture sites organized by arrays of micro-ellipse microposts enduring less stress. Circular elliptical microstructures produce smooth flow minimally reducing any damage. “Air Suction” could extremely shorten capture. Capture efficiency comes out to be a robust yield of 90% and percentage obeys Gaussian distribution at various stages. With rare number accurately enumerated, micro-Ellipse filters have been tested high efficiently capturing tumor cells in both whole and lysed blood. To clinically validate the device, the microfluidic chip was utilized to identify and capture CTCs from metastatic breast, colon and non-small-cell lung (NSCLC) cancer patients. CTCs were detected positive in all samples with 4 patients having more than 20 CTCs. Those sensitive results are consistent with theoretical expectation. Efficient micro-ellipse filters enable clinical enumeration of metastasis, on-chip anti-cancer drug responses and biological molecular analysis.